Prevalence and correlates of symptoms of depression, anxiety, and psychological distress among women of reproductive age with delayed conception in urban and peri-urban low to mid-socioeconomic neighborhoods of Delhi, India: A cross-sectional study. - Barsha Gadapani Pathak; Gitau Mburu; Ndema Habib; Rita Kabra; Aiysha Malik; James Kiarie; Ranadip Chowdhury; Neeta Dhabhai; Sarmila Mazumder (PLoS ONE)
Introduction One in six people of reproductive age experience infertility in their lifetime. Infertility can have significant impacts on mental health. Psychological distress is a broad term encompassing emotional suffering and mental health discomfort that can include symptoms of anxiety and depression but is not limited to these conditions. We investigated the prevalence of symptoms of depression, anxiety, and psychological distress and their associated risk factors among women of reproductive age with delayed conception. Methods A total of 1530 women were recruited from community settings in Northern India. Quantitative data were collected using a 4-item Patient Health Questionnaire-4 (PHQ-4) which is an ultra-brief self-report questionnaire consisting of a 2-item depression scale (PHQ-2) and a 2-item anxiety scale (generalized anxiety depression-2). Data were collected between July 2020 and August 2021. Descriptive analysis was conducted to summarise the characteristics and prevalence of symptoms of depression, anxiety, and psychological distress. Logistic regression was used to identify risk factors for psychological distress. Results We obtained responses from all 1,530 women using these scales. Over half (54.31%) of participants had psychological distress, of whom 38.10% were experiencing mild distress, 10.59% moderate distress, and 5.62% severe distress. Additionally,16.07% of participants reported symptoms of anxiety and 20% reported symptoms of depression. Factors associated with psychological distress were: (i) a higher total number of children that women intended to have in their lifetime, (ii) longer duration of trying to get pregnant (> 18 months), (iii) continuous effort trying to achieve pregnancy, (iv) women's perception that conception is taking long, (v) social isolation, (vi) being emotionally or verbally abused by husband and family members, and (vii) having other co-morbidities such as hypertension, irregular menstrual cycles, irregular bleeding between regular cycles, abnormal vaginal discharge or pain during sex. Conclusion This study demonstrates the high mental health burden faced by women with delayed conception in low- to mid-socioeconomic neighbourhoods of North India including high levels of anxiety and depression. To better support individuals and couples achieve their reproductive goals, we advocate for the integration of psychosocial interventions to improve mental health outcomes and promote the well-being of those facing delays in achieving pregnancy. Specifically, addressing social isolation, fostering supportive networks, combating violence towards women, and incorporating fertility counselling and group-based psychosocial interventions within community and healthcare settings are needed to alleviate mental health symptoms among women who have difficulties in conceiving. However, the successful implementation of these recommendations may be challenged by the availability of the state's healthcare resources, necessitating tailored strategies with contextual adaptations.